Measurements and modeling of snow albedo at Alerce Glacier, Argentina: effects of volcanic ash, snow grain size and cloudiness - Gelman Constantin, Julián (2020)
The relevance of light absorbing impurities in snow albedo (and its effects in seasonal snow or glacier mass balance) have been under study for several decades. However, the effect of volcanic ash has been much less studied, and most articles studied only the effect of thick layers after direct deposition. There is also a knowledge gap in field measurements of seasonal snow and glaciers of the southern Andes, that only recently has started to be filled.We present here the first field measurements on Argentinian Andes, combined with albedo and mass balance modeling activities.Measured impurities content (1.1mgkg−1 to 30000 mgkg−1) varied abruptly in snow pits and snow/firn cores, due to high surface enrichment during ablation season and possibly local/regional wind driven resuspension and redeposition of dust and volcanic ash. In addition, we observed a high spatial hetereogeneity, due to seasonality, glacier topography and prevailing wind direction. Microscopical characterization showed that the major component was ash from recent Calbuco (2015) and Cordón Caulle (2011) volcanic eruption, with 10 minor presence of mineral dust and Black Carbon. We also found a wide range of measured snow albedo (0.26 to 0.81), whichreflected mainly the impurities content and the snow/firn grain size (due to aging). SNICAR model has been updated to model snow albedo taking into account the effect of cloudiness on incident radiation spectra, improving the match of modeled and measured values. We also ran sensitivity studies on the main measured parameters (impurities content and composition, snow grain size, layer thickness, etc) to assess which field measurements precision can improve the uncertainty of albedo modeling. Finally, we studied the impact of these albedo reductions in Alerce glacier using a spatially distributed surface mass-balance model. We found a large impact of albedo changes in glacier mass balance, and we estimated that the effect of observed ash concentrations can be as high as a 1.25mwe decrease in the glacier-wide annual mass balance (due to a 34 % of increase inthe melt during the ablation season).